Mitigation of Acrylamide in Potato Chips by Pre-drying and Pulsed Electric Field Treatment - Liu, Caiyun; Zhang, Rui; Vorobiev, Eugene; Grimi, Nabil (Frontiers in Nutrition, 2022)
The object of this work was to study the effects of preliminary vacuum drying (VD), pulsed electric field (PEF) treatment and frying temperature on colour, oil uptake and acrylamide content in fried potato chips. Results indicated that an increase of frying temperature from 120°C to 180°C leaded to a decrease of frying time around 70% for untreated and PEF pre-treated samples. The colour value of L* and a* decreased with the increase of frying temperature, and those values of sample pretreated by PEF were significantly higher compared to those obtained from untreated samples. PEF pretreatment promoted the reduction of oil content of fried sample by up to 17.6%, 14.2%, and 16% compared with untreated samples at the frying temperature of 120°C, 150°C and 180°C, respectively. Higher efficiency was observed by applying the preliminary VD in the case of the frying temperature of 150°C. Furthermore, it was revealed that PEF pretreatment and preliminary VD application leads to a synergetic effect on the reduction of acrylamide content in the potato chips. For example, with the initial moisture ratio of 0.5 pre-dried by VD and pre-treated by PEF, the acrylamide content was noticeably decreased from 2220 μg/kg to 311 μg/kg compared to untreated and undehydrated sample at the frying temperature of 150°C. Our findings provide reference for new pretreatment to mitigate acrylamide formation and to improve the quality of potato chips.